CONFLICT MANAGEMENT OF SCHOOL ADMINISTRATORS UNDER SUKHOTHAI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Makjeen, Mongkhon; NakAi, Nikom (Journal of MCU Nakhondhat, 2024)
This research paper aims to 1) study the level of conflict management of school administrators 2) To study appropriate approaches to conflict management of school administrators. Affiliated with the Sukhothai Primary Education Area Office District 1 using a hybrid research methodology. Using quantitative and qualitative data collection methods, the population and the informant group are school administrators under the Sukhothai Primary Education Area Office. District 1, with a total of 124 schools, uses a selective method. The instruments used in the research were a 5 - level estimation scale questionnaire, 1 - answer form, and an interview form. The statistics used in the data analysis are confidence, percentage, mean, standard deviation, and interview data analysis from frequency values. The results showed that 1) conflict management among school administrators was very high overall (μ = 3.80, σ = 0.59), when looking at each aspect, it was found that the side with the highest average was focused on compromise (μ = 4.58, σ = 0.64), followed by focusing on cooperation (μ = 4.52, σ = 0.71), and the side with the lowest average was emphasizing winning (μ = 2.45, σ = 1.26). School administrators must do everything in accordance with the regulations. Correct regulations 2.2) Emphasis on cooperation School administrators must provide opportunities for all personnel to ask questions and grievances to create mutual understanding. 2.3) Emphasizing compromise School administrators must be impartial. Fair and moral 2.4) Avoidance Emphasis School administrators must avoid confronting conflicts that are personal to individuals. 2.5) Emphasis on allowing school administrators to pay attention to suggestions and listen to the opinions of personnel.